HZSM-5 molecular sieve as well as preparation method and application thereof

By loading platinum nanoparticles on HZSM-5 molecular sieve, the problem of insufficient catalyst activity and selectivity in the existing biomass hydrodeoxygenation technology is solved, and efficient hydrodeoxygenation and product selectivity of biooils are achieved.

CN119702057AActive Publication Date: 2025-03-28SUN YAT SEN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411890091.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In the existing biomass hydrodeoxygenation technology, the catalyst activity and selectivity are insufficient, resulting in low upgrading efficiency of bio-oil and many side reactions, affecting the quality of the product.

Method used

Using HZSM-5 molecular sieve as a catalyst, a catalytic system with excellent hydrogenation effect is formed by supporting platinum nanoparticles on its sheet-like matrix. The ultrathin sheet-like structure of the molecular sieve and the uniform distribution of platinum nanoparticles improve catalytic activity and selectivity.

Benefits of technology

It realizes efficient hydrodeoxygenation of biooil under lower temperature and pressure conditions, significantly improves the selectivity and conversion of 2-methoxy-4-methylphenol, reduces the occurrence of side reactions, and improves the stability and sustainability of the catalytic system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702057A_ABST
    Figure CN119702057A_ABST
Patent Text Reader

Abstract

The invention discloses an HZSM-5 molecular sieve as well as a preparation method and application thereof. The HZSM-5 molecular sieve comprises a flaky HZSM-5 molecular sieve matrix and platinum nanoparticles loaded on the flaky HZSM-5 molecular sieve matrix, the average thickness of the flaky HZSM-5 molecular sieve matrix is 50 to 100 nm. The sheet-shaped HZSM-5 molecular sieve matrix can provide an acid center, the platinum nanoparticles can provide a hydrogenation center, and good catalytic activity can be achieved through cooperation of the sheet-shaped HZSM-5 molecular sieve matrix and the platinum nanoparticles; moreover, the sheet-shaped HZSM-5 molecular sieve matrix has relatively thin thickness, namely relatively short b-axis hole channel length, so that not only is substance diffusion and transmission facilitated, but also the condition of side reaction caused by contact of an intermediate product with an acidic site can be greatly reduced, so that higher product selectivity can be provided. Particularly, the HZSM-5 molecular sieve disclosed by the invention has a good application prospect in catalysis of hydrodeoxygenation of bio-oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic chemical synthesis, and in particular relates to a HZSM-5 molecular sieve and a preparation method and application thereof. Background Art

[0002] Biomass has attracted extensive attention as one of the most important renewable resources on earth and a renewable resource that can be converted into liquid fuels. The main components of biomass are cellulose, hemicellulose and lignin. Cellulose and hemicellulose are composed of complex polysaccharides; lignin is a highly substituted mononuclear phenolic amorphous polymer composed of phenylpropane units, and its precursors are three lignin monomers, including p-coumaryl alcohol, coniferyl alcohol and sinapyl alcohol.

[0003] Biomass conversion can be mainly divided into the following categories: (1) Direct combustion technology: Direct combustion has high requirements for raw materials, is inefficient and environmentally unfriendly; (2) Bioconversion technology: Biomass is converted into ethanol and the like by utilizing microbial fermentation; (3) Thermal conversion technology: Generally divided into three methods: gasification, pyrolysis and liquefaction. Among them, biomass pyrolysis is the process of thermal decomposition of organic compounds under anaerobic conditions to obtain coke, syngas and bio-oil. However, bio-oil contains a large amount of oxygen-containing compounds such as acids, ketones and esters, which not only has low calorific value but also unstable combustion, making it difficult to use directly. Therefore, additional bio-oil upgrading processes are required to obtain higher quality chemicals. Hydrodeoxygenation (HDO) is considered to be an effective process for deoxygenating bio-oil. The HDO of bio-oil needs to be carried out under a certain temperature and hydrogen environment. The reactions that may occur during the catalytic process include: (1) water separation; (2) dehydration reaction caused by condensation reaction; (3) decarboxylation reaction, in which oxygen is removed in the form of H2O; (4) hydrogenation reaction, which may involve saturation of unsaturated components; (5) hydrogenolysis reaction, which is related to the breaking of CO bonds, in which oxygen can be released in the form of water; (6) hydrocracking reaction, which involves the decomposition of high molecular components into smaller molecules.

[0004] In the research field of biomass hydrodeoxygenation, supported catalysts of transition metals or precious metals are the most eye-catching, and vanillin, as a very representative simple phenolic lignin model compound, has received more attention and research. For example, a study reported a Ni-P amorphous alloy material synthesized by chemical reduction. After adding Co modification, it not only increased the number of active centers of the catalyst, but also improved the dispersion, thermal stability and disorder of the amorphous alloy. Under the conditions of H2 partial pressure of 2.0MPa, reaction temperature of 150℃ and reaction time of 3h, the conversion rate of vanillin and the selectivity of 2-methoxy-4-methylphenol can reach 100% and 82.7%, respectively. In addition, there are studies that distribute metal organic framework (MOF) ZIF-67 on carbonaceous matrix (Ni xCo@NC@C) precursor method was used to develop bimetallic Ni-Co nanoparticles coated with hierarchical flower-like nitrogen-doped carbon layers. 2+ The etching ions were treated hydrothermally with glucose; the results showed that the defective oxygen vacancies on the catalyst and the rich electrons provided by Co enabled it to achieve complete conversion of vanillin under mild conditions. In addition, the mesoporous ZrO2 prepared by precipitation method was studied, and the yield of 2-methoxy-4-methylphenol could reach 99% under the conditions of 5.0MPa H2 partial pressure, 180℃ reaction temperature and 24h reaction in isopropanol solvent. Summary of the invention

[0005] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a HZSM-5 molecular sieve, which has a small average thickness (i.e., a small b-axis pore length), which is not only conducive to material diffusion and transmission, but also can greatly reduce the situation where intermediate products contact acidic sites and cause side reactions, thereby providing higher reaction selectivity; in addition, combined with the excellent hydrogenation effect of platinum, it is beneficial for the molecular sieve to achieve good hydrogenation deoxygenation activity.

[0006] A second object of the present invention is to provide a method for preparing the above-mentioned HZSM-5 molecular sieve.

[0007] The third object of the present invention is to provide an application of the above HZSM-5 molecular sieve in catalytic hydrodeoxygenation of bio-oil.

[0008] A fourth object of the present invention is to provide a method for preparing 2-methoxy-4-methylphenol.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is:

[0010] The first aspect of the present invention provides a HZSM-5 molecular sieve, comprising a flaky HZSM-5 molecular sieve substrate and platinum nanoparticles loaded on the flaky HZSM-5 molecular sieve substrate; the average thickness of the flaky HZSM-5 molecular sieve substrate is 50 to 100 nm.

[0011] Preferably, the average thickness of the flaky HZSM-5 molecular sieve matrix is ​​60 to 90 nm, and more preferably 70 to 85 nm.

[0012] In the present invention, the thickness of the sheet-like HZSM-5 molecular sieve matrix is ​​the b-axis pore length thereof.

[0013] Preferably, the average diameter of the platinum nanoparticles is 8 to 15 nm; more preferably, it is 10 to 12 nm.

[0014] Preferably, in the HZSM-5 molecular sieve, silicon and aluminum are measured as SiO2 and Al2O3, respectively, and the molar ratio of silicon to aluminum is 1:(0.001-0.02); more preferably 1:(0.002-0.01); and even more preferably 1:(0.003-0.007).

[0015] Preferably, in the HZSM-5 molecular sieve, the mass percentage of platinum nanoparticles is 0.1-1%; more preferably 0.15-0.8%; and even more preferably 0.2-0.5%.

[0016] The second aspect of the present invention provides a method for preparing an HZSM-5 molecular sieve, comprising the following steps: mixing a silicon source, an aluminum source, sodium hydroxide, a template, urea, isopropanol and water, and sequentially performing a crystallization reaction, a first calcination, an ammonium exchange reaction and a second calcination to obtain a flaky HZSM-5 molecular sieve matrix; mixing the flaky HZSM-5 molecular sieve matrix with a platinum source, and performing a third calcination to obtain the HZSM-5 molecular sieve as described in the first aspect of the present invention.

[0017] The preparation method of the present invention first synthesizes an ultra-thin sheet HZSM-5 molecular sieve matrix, and then loads platinum, so as to obtain the required material in a simple and efficient manner; wherein, by adding urea, the b-axis pore length of the sheet HZSM-5 molecular sieve matrix can be precisely controlled; and isopropanol can be used as an auxiliary solvent or dispersant, and isopropanol can help to evenly disperse silicon sources, aluminum sources, template agents and urea in the system, thereby avoiding aggregation or precipitation of components in the system, and isopropanol has suitable molecular polarity and molecular size, and can promote the crystallization reaction to proceed better.

[0018] Preferably, the silicon source is selected from tetraethoxysilane.

[0019] Preferably, the aluminum source is selected from aluminum nitrate nonahydrate.

[0020] Preferably, the template is selected from tetrapropylammonium hydroxide (TPAOH).

[0021] In the reaction system, both TPAOH and NaOH will dissociate into OH - Therefore, the alkaline environment in the synthesis system is provided by TPAOH and NaOH, and the main role of NaOH is to assist in regulating alkalinity, adjusting the crystallization rate and balancing the charge of the molecular sieve framework.

[0022] The present invention can prepare a molecular sieve with better performance by selecting a specific silicon source, an aluminum source and a template agent, combining sodium hydroxide, urea and isopropanol, and performing specific crystallization, ammonium exchange, roasting and platinum loading processes.

[0023] Preferably, the ammonium source used in the ammonium exchange reaction includes ammonium chloride, ammonium nitrate or a combination thereof; further preferably, the ammonium source used in the ammonium exchange reaction is selected from ammonium chloride.

[0024] Preferably, the platinum source includes at least one of tetraammine platinum nitrate, chloroplatinic acid, platinum tetrachloride or dichloroplatinous acid; further preferably, the platinum source includes at least one of tetraammine platinum nitrate, platinum tetrachloride or dichloroplatinous acid; even more preferably, the platinum source is selected from tetraammine platinum nitrate.

[0025] Preferably, the silicon source and the aluminum source are measured as SiO2 and Al2O3 respectively, and the molar ratio of the silicon source to the aluminum source is 1:(0.001-0.02); more preferably 1:(0.002-0.01); and even more preferably 1:(0.003-0.007).

[0026] Preferably, the silicon source is measured as SiO2, and the molar ratio of the silicon source to the sodium hydroxide is 1:(0.01-0.2); more preferably 1:(0.02-0.1); and even more preferably 1:(0.03-0.07).

[0027] Preferably, the silicon source is measured as SiO2, and the molar ratio of the silicon source to the template is 1:(0.1-2); more preferably 1:(0.2-1); and even more preferably 1:(0.3-0.7).

[0028] Preferably, the silicon source is measured as SiO2, and the molar ratio of the silicon source to the urea is 1:(0.3-2); more preferably 1:(0.4-1.5); and even more preferably 1:(0.5-1).

[0029] Preferably, the silicon source is measured as SiO2, and the molar ratio of the silicon source to the isopropanol is 1:(0.01-0.2); more preferably 1:(0.02-0.1); and even more preferably 1:(0.03-0.07).

[0030] Preferably, the ammonium source used in the ammonium exchange reaction participates in the reaction in the form of an aqueous solution; further preferably, the ammonium concentration in the aqueous solution of the ammonium source is 0.1 to 2 mol / L; further preferably, it is 0.5 to 1.5 mol / L.

[0031] Preferably, the ammonium source used in the ammonium exchange reaction is measured in ammonium, and the usage ratio of the ammonium source to the product of the first calcination is (0.001-0.02) mol: 1 g; more preferably (0.005-0.015) mol: 1 g.

[0032] Preferably, the platinum source participates in the reaction in the form of an aqueous solution; more preferably, the Pt concentration in the aqueous solution of the platinum source is 0.1 to 2 g / L; more preferably, it is 0.2 to 1 g / L.

[0033] Preferably, the platinum source is measured as Pt, and the mass ratio of the platinum source to the flaky HZSM-5 molecular sieve matrix is ​​(0.0005-0.01):1; more preferably (0.001-0.007):1; and even more preferably (0.0015-0.004):1.

[0035] Preferably, in the preparation method, the mixing order of the raw materials is: template, silicon source, isopropanol, urea, aluminum source, sodium hydroxide and water.

[0036] Preferably, the temperature of the crystallization reaction is 160-200°C; more preferably, 170-190°C.

[0037] Preferably, the crystallization reaction time is 24 to 72 hours; more preferably, it is 36 to 60 hours.

[0038] Preferably, the temperature rise rate of the crystallization reaction is 10-20° C. / h; more preferably, 13-17° C. / h.

[0039] In some embodiments of the present invention, the crystallization reaction further includes a step of collecting the crystallization product. The step of collecting the crystallization product is well known to those skilled in the art, and common operations include centrifuging, washing and drying the crystallization product.

[0040] Preferably, the calcination temperature of the first calcination and the calcination temperature of the second calcination are each independently 500-600°C; more preferably 530-570°C.

[0041] Preferably, the holding time of the first calcination and the holding time of the second calcination are each independently 2 to 8 hours; more preferably 4 to 6 hours.

[0042] Preferably, the heating rate of the first calcination and the heating rate of the second calcination are independently 80 to 120° C. / h; more preferably, 90 to 110° C. / h.

[0043] Preferably, the reaction temperature of the ammonium exchange reaction is 60-100°C; more preferably, it is 70-90°C.

[0044] Preferably, the reaction time of the ammonium exchange reaction is 1 to 4 hours; more preferably, it is 1.5 to 3 hours.

[0045] In some embodiments of the present invention, the method of mixing the flaky HZSM-5 molecular sieve matrix with the platinum source is selected from the impregnation method.

[0046] Preferably, the calcination temperature of the third calcination is 300-500°C; more preferably, 320-450°C.

[0047] Preferably, the holding time of the third calcination is 2 to 8 hours; more preferably, it is 3 to 6 hours.

[0048] Preferably, the heating rate of the third calcination is 0.5 to 5°C / min; more preferably, it is 0.8 to 2°C / min.

[0049] Preferably, the third calcination includes a first stage calcination and a second stage calcination; the first stage calcination is carried out in an atmosphere of oxygen-containing gas; and the second stage calcination is carried out in an atmosphere of reducing gas.

[0050] Preferably, the oxygen-containing gas comprises oxygen or air; more preferably air.

[0051] Preferably, the reducing gas includes at least one of hydrogen, carbon monoxide or methane; more preferably hydrogen.

[0052] Preferably, the calcination temperature of the first stage calcination is 30-70°C higher than the calcination temperature of the second stage calcination; more preferably, it is 40-60°C higher.

[0053] By adopting a specific calcination temperature, the HZSM-5 molecular sieve can be calcined completely, and the platinum nanoparticles can be evenly dispersed in the flaky HZSM-5 molecular sieve matrix to avoid a large amount of agglomeration.

[0054] Preferably, the ratio of the holding time of the first stage calcination to the holding time of the second stage calcination is 1:(0.5-2); more preferably, it is 1:(0.8-1.2).

[0055] Preferably, the calcination temperature of the first stage calcination is 300-500°C; more preferably, 350-400°C.

[0056] Preferably, the holding time of the first stage calcination is 1 to 4 hours; more preferably, it is 1.5 to 3 hours.

[0057] Preferably, the heating rate of the first stage calcination is 0.1-5°C / min; more preferably, it is 0.3-2°C / min.

[0058] Preferably, the calcination temperature of the second stage calcination is 300-400°C; more preferably, 320-350°C.

[0059] Preferably, the holding time of the second stage calcination is 1 to 4 hours; more preferably, it is 1.5 to 3 hours.

[0060] Preferably, the heating rate of the second stage calcination is 0.1-5°C / min; more preferably, it is 0.3-2°C / min.

[0061] The third aspect of the present invention provides a use of the HZSM-5 molecular sieve described in the first aspect of the present invention in catalytic hydrodeoxygenation of bio-oil.

[0062] Preferably, the bio-oil comprises at least one of acids, ketones, esters, aldehydes or phenols; further preferably, the bio-oil comprises aldehydes, phenols or a combination thereof.

[0063] In some embodiments of the present invention, the bio-oil is selected from phenolic lignin; in some specific embodiments of the present invention, the bio-oil is selected from vanillin.

[0064] Vanillin is a simple phenolic lignin. The HZSM-5 molecular sieve of the present invention has a good catalytic effect in the hydrodeoxygenation of vanillin, and can prepare 2-methoxy-4-methylphenol with high activity and high selectivity.

[0065] The fourth aspect of the present invention provides a method for preparing 2-methoxy-4-methylphenol, comprising the following steps: using the HZSM-5 molecular sieve described in the first aspect of the present invention as a catalyst and vanillin as a substrate to carry out a hydrodeoxygenation reaction to obtain 2-methoxy-4-methylphenol.

[0066] Preferably, the hydrodeoxygenation reaction is carried out in a hydrogen atmosphere; the partial pressure of the hydrogen is 1 to 3 MPa; more preferably 1.5 to 2.5 MPa.

[0067] Preferably, the reaction temperature of the hydrodeoxygenation reaction is 80-160°C; more preferably 100-140°C; further preferably 110-130°C.

[0068] Preferably, the reaction time of the hydrodeoxygenation reaction is 30 to 300 min; more preferably 50 to 200 min; further preferably 100 to 150 min.

[0069] Preferably, the molar ratio of the vanillin to the platinum nanoparticles in the HZSM-5 molecular sieve is (400-1000):1; more preferably (450-800):1; and even more preferably (480-600):1.

[0070] Preferably, the hydrodeoxygenation reaction is carried out in water; more preferably, the mass ratio of the vanillin to the water is 1:(100-400); more preferably, it is 1:(200-300).

[0071] The beneficial effects of the present invention are as follows: the flaky HZSM-5 molecular sieve matrix of the present invention can provide acidic centers, and the platinum nanoparticles can provide hydrogenation centers, and the combination of the two can achieve good catalytic activity; and the flaky HZSM-5 molecular sieve matrix has a thinner thickness, that is, a shorter b-axis pore length, which is not only conducive to material diffusion and transmission, but also can greatly reduce the situation where the intermediate product contacts the acidic site and causes side reactions, so that higher product selectivity can be provided. The HZSM-5 molecular sieve of the present invention has a particularly good hydrodeoxygenation effect, and in particular, it has a good application prospect in catalyzing bio-oil hydrodeoxygenation.

[0072] Specifically, compared with the prior art, the present invention has the following advantages:

[0073] 1. The HZSM-5 molecular sieve provided by the present invention has a good effect in catalyzing the hydrodeoxygenation of vanillin to produce 2-methoxy-4-methylphenol. Specifically, the platinum nanoparticles in the HZSM-5 molecular sieve have good hydrogenation activity, which is beneficial to the conversion of vanillin into vanillyl alcohol, while the flaky HZSM-5 molecular sieve matrix can provide an acidic center to achieve a dehydroxylation process, and the short b-axis of the flaky HZSM-5 molecular sieve matrix can also prevent the intermediate product from reacting with its acidic site, so that the product 2-methoxy-4-methylphenol can be obtained with high selectivity, thereby achieving high activity and high selectivity for preparing 2-methoxy-4-methylphenol by hydrodeoxygenation of vanillin, as well as the stability and sustainability of the catalytic system.

[0074] 2. In the preparation method of the HZSM-5 molecular sieve provided by the present invention, an ultra-thin sheet HZSM-5 molecular sieve matrix is ​​first synthesized, and then platinum is loaded to obtain the required material in a simple and efficient manner; in addition, mainly by adding urea and regulating the amount of urea, the b-axis pore length of the sheet HZSM-5 molecular sieve matrix can be precisely controlled. The process is simple and easy, and the obtained HZSM-5 molecular sieve has good catalytic activity and selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 2 is the XRD spectrum of sample A2 and sample A3 in Example 1 of the present invention.

[0076] Figure 2 2 is the SEM image and particle size distribution diagram of sample A2 in Example 1 of the present invention.

[0077] Figure 3TEM image and particle size distribution diagram of sample A3 in Example 1 of the present invention.

[0078] Figure 4 The SEM image and particle size distribution diagram of sample B2 in comparative example 1 of the present invention.

[0079] Figure 5 TEM image and particle size distribution diagram of sample B3 in comparative example 1 of the present invention. DETAILED DESCRIPTION

[0080] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.

[0081] Example 1

[0082] This example provides a platinum metal nanocluster ultra-thin HZSM-5 molecular sieve, and the specific preparation steps are as follows:

[0083] 1) Weigh 0.1g of isopropyl alcohol (IPA) and dissolve it in 2g of H2O to obtain solution A; Weigh 2g of urea and dissolve it in 4g of H2O to obtain solution B; Weigh 0.3g of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and dissolve it in 4g of H2O to obtain solution C; Weigh 0.1g of sodium hydroxide (NaOH) and dissolve it in 2g of H2O to obtain solution D. Weigh 8.19g of tetrapropylammonium hydroxide (TPAOH 40wt%) and stir at room temperature, slowly drop 11.2g of tetraethoxysilane (TEOS), then add A, B, C, D solutions and 11.31g of H2O in sequence, and continue stirring for 2h to form a system for synthesizing ultrathin NaZSM-5 molecular sieves.

[0084] In the synthetic ultra-thin NaZSM-5 molecular sieve system:

[0085] The molar ratio of SiO2, Al2O3, and NaOH is 1.0:0.0042:0.046;

[0086] The molar ratio of tetrapropylammonium hydroxide, isopropyl alcohol, urea and tetraethoxysilane is 0.3:0.031:0.62:1, and tetraethoxysilane is calculated as SiO2.

[0087] 2) The mixed solution was then placed in a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and the temperature was raised to 180°C at a heating rate of 15°C / h and allowed to stand for crystallization for 2 days. After the crystallization was completed, the reactor was taken out and quickly cooled to room temperature with water, and the crystallized product was centrifuged, washed, and dried. The obtained sample was calcined in a muffle furnace at a temperature of 550°C, a time of 5h, and a heating rate of 100°C / h. Sample A1 was obtained.

[0088] 3) Then weigh NH4Cl and dissolve it in water to prepare a 1 mol / L NH4Cl aqueous solution. Take 1 g of sample A1 and heat it in a water bath at 80°C and a stirring rate of 600 rpm, add 10 mL of NH4Cl aqueous solution, and keep it for 2 hours to perform ammonium exchange.

[0089] In the system for ammonium exchange of the ultrathin NaZSM-5 molecular sieve, the volume ratio of the sample A1 mass to the 1 mol / L NH4Cl aqueous solution is 1:10.

[0090] 4) After the ammonium exchange is completed, the product is centrifuged and washed, and the ammonium exchange in step 3) is repeated twice. Then, the product is dried and calcined in a muffle furnace at a temperature of 550°C, a time of 5h, and a heating rate of 100°C / h to obtain sample A2, i.e., HZSM-5 molecular sieve.

[0091] 5) Then, using tetraammine platinum nitrate as a platinum precursor, platinum was loaded onto sample A2 by impregnation. 1 g of sample A2 was weighed and dispersed in 5 g of H2O and stirred continuously for 2 h, and then 0.004 g of tetraammine platinum nitrate was dissolved in 10 mL of H2O to prepare solution E. Solution E was slowly dripped into the uniformly dispersed ultra-thin HZSM-5 mixed solution under stirring at room temperature.

[0092] In the synthetic platinum metal nanocluster ultra-thin HZSM-5 molecular sieve system:

[0093] The mass ratio of sample A2 to platinum is 1.0:0.002;

[0094] The volume ratio of the mass of sample A2 to the tetraammineplatinum nitrate aqueous solution is 1:15.

[0095] 6) After continuous stirring at room temperature for 4 hours, the product was evaporated and dried, calcined in a tube furnace with flowing air at a temperature of 500°C, a time of 2 hours, and a heating rate of 1°C / min, and then reduced in a hydrogen atmosphere at a temperature of 400°C, a time of 2 hours, and a heating rate of 1°C / min. Sample A3, i.e., ultrathin HZSM-5 molecular sieve of platinum metal nanoclusters, was obtained.

[0096] Figure 1The XRD spectra of sample A2 and sample A3 in Example 1 of the present invention are shown in the figure. It can be seen that the prepared samples A2 and A3 are both HZSM-5 molecular sieves; the peaks are sharp and free of impurities, and there is no obvious characteristic peak of platinum element in the molecular sieve spectrum, indicating that the molecular sieve has high crystallinity. At the same time, in sample A3, the platinum loaded on the molecular sieve has no obvious agglomeration.

[0097] Figure 2 It is the SEM image and particle size distribution diagram of sample A2 in Example 1 of the present invention. The small figure in the upper right corner is the particle size distribution diagram. It can be seen from the figure that the synthesized molecular sieve crystal morphology is regular. From the particle size analysis results, it can be obtained that the b-axis channel length of the ultra-thin HZSM-5 is about 75.8nm.

[0098] Figure 3 The TEM image and particle size distribution diagram of sample A3 in Example 1 of the present invention. The small image in the upper left corner is the particle size distribution diagram; the dark black spots in the TEM image are platinum nanoclusters, which are composed of Figure 3 It can be seen that the platinum nanoclusters are evenly dispersed in the ultrathin HZSM-5 molecular sieve crystals, and from the particle size analysis results, it can be seen that the diameter distribution of the platinum nanoclusters is relatively uniform, with an average diameter of about 11.42nm.

[0099] The silicon-aluminum ratio (SiO2:Al2O3) of sample A1 is 1.00:0.0042.

[0100] The mass fraction of platinum in sample A1 is about 0.2%.

[0101] Comparative Example 1

[0102] This example provides a platinum metal nanocluster HZSM-5 molecular sieve. Different from Example 1, this comparative example uses a traditional HZSM-5 molecular sieve as a carrier, and the platinum nanocluster is loaded by the same impregnation method.

[0103] The difference between this comparative example and Example 1 is that the conventional HZSM-5 molecular sieve with a longer b-axis pore length is used to support the platinum nanoclusters.

[0104] The specific implementation method of this comparative example is as follows:

[0105] 1) Weigh 0.13 g of NaOH and dissolve it in 19.45 g of H2O to prepare solution A, then weigh 0.05 g of sodium aluminate and add it to solution A, add 5.08 g of tetrapropylammonium hydroxide (TPAOH 40 wt%) under stirring, and then slowly drop 10.71 g of TEOS into the system, and stir at 600 rpm for at least 4 h at room temperature (25°C) using a stirring magnet to form a system for synthesizing a conventional NaZSM-5 molecular sieve.

[0106] In the synthetic NaZSM-5 molecular sieve system:

[0107] The molar ratio of SiO2, NaAlO2, NaOH and tetrapropylammonium hydroxide is 1.0:0.0059:0.632:0.195.

[0108] 2) The mixed solution was then placed in a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and the temperature was raised to 170°C at a heating rate of 2°C / min and allowed to stand for crystallization for 3 days. After the crystallization was completed, the hydrothermal reactor was naturally cooled and the reactor was taken out. The crystallized product was centrifuged, washed and dried. The obtained sample was calcined in a muffle furnace at a temperature of 550°C, a time of 5h, and a heating rate of 100°C / h. Sample B1 was obtained.

[0109] 3) Then weigh NH4Cl and dissolve it in water to prepare a 1 mol / L NH4Cl aqueous solution. Take 1 g of sample B1 and heat it in a water bath at 80°C and a stirring rate of 600 rpm, then add 10 mL of the NH4Cl aqueous solution and keep it for 2 hours.

[0110] In the system for ammonium exchange of the NaZSM-5 molecular sieve, the volume ratio of the sample B1 mass to the 1 mol / L NH4Cl aqueous solution is 1:10.

[0111] 4) After the ammonium exchange is completed, the product is centrifuged and washed, and the ammonium exchange in step 3) is repeated twice. After the product is dried, it is calcined in a muffle furnace at a temperature of 550° C., a time of 5 h, and a heating rate of 100° C. / h to obtain sample B2.

[0112] 5) Then, using tetraammine platinum nitrate as a platinum precursor, platinum was loaded on sample B2 by impregnation method. 1 g of sample B2 was weighed and dispersed in 5 g of H2O and stirred continuously for 2 h, and then 0.004 g of tetraammine platinum nitrate was dissolved in 10 mL of H2O to prepare solution B. Solution B was slowly dripped into the evenly dispersed HZSM-5 mixed solution under stirring at room temperature.

[0113] In the synthetic platinum metal nanocluster HZSM-5 molecular sieve system:

[0114] The mass ratio of B2 to platinum is 1.0:0.002;

[0115] The volume ratio of the mass of sample B2 to the tetraammineplatinum nitrate aqueous solution is 1:15.

[0116] 6) After continuous stirring at room temperature for 4 h, the product was evaporated and dried, calcined in a tube furnace with flowing air at a temperature of 500° C. for 2 h at a heating rate of 1° C. / min, and then reduced in a hydrogen atmosphere at a temperature of 400° C. for 2 h at a heating rate of 1° C. / min. Sample B3 was obtained.

[0117] Figure 4 The SEM image and particle size distribution diagram of sample B2 in comparative example 1 of the present invention are shown in the lower left corner. The small image is the particle size distribution diagram. It can be seen that the synthesized molecular sieve crystals have a regular morphology. From the particle size analysis results, it can be obtained that the b-axis pore length of the HZSM-5 molecular sieve is about 181nm. Figure 2 and Figure 4 By comparison, it can be seen that the b-axis channel size of sample B3 in comparative example 1 is significantly longer than the b-axis channel size of ultra-thin HZSM-5 sample A3 in example 1.

[0118] Figure 5 It is the TEM image and particle size distribution diagram of sample B3 in comparative example 1 of the present invention. The small image in the lower right corner is the particle size distribution diagram. The dark black spots in the TEM image are platinum nanoclusters. It can be seen from the figure that the platinum nanoclusters are uniformly dispersed in the HZSM-5 molecular sieve crystals. It can be seen from the particle size analysis results that the diameter distribution of the platinum nanoclusters is relatively uniform, and the average diameter is about 11.74nm.

[0119] The silicon-aluminum ratio (SiO2:Al2O3) of sample B1 is 1.00:0.00295.

[0120] The mass fraction of platinum in sample B1 is about 0.2%.

[0121] Example 2

[0122] This example provides a platinum metal nanocluster ultra-thin HZSM-5 molecular sieve, and the specific preparation steps are as follows:

[0123] 1) Weigh 0.1g of isopropyl alcohol (IPA) and dissolve it in 2g of H2O to obtain solution A; Weigh 2g of urea and dissolve it in 4g of H2O to obtain solution B; Weigh 0.3g of aluminum nitrate (Al(NO3)3·9H2O) and dissolve it in 4g of H2O to obtain solution C; Weigh 0.1g of sodium hydroxide (NaOH) and dissolve it in 2g of H2O to obtain solution D. Weigh 8.19g of tetrapropylammonium hydroxide (TPAOH 40wt%) and stir at room temperature, slowly drop 11.2g of tetraethoxysilane (TEOS), then add A, B, C, D solutions and 11.31g of H2O in sequence, and continue stirring for 2h to form a system for synthesizing ultrathin NaZSM-5 molecular sieves.

[0124] In the synthetic ultra-thin NaZSM-5 molecular sieve system:

[0125] The molar ratio of SiO2, Al2O3, and NaOH is 1.0:0.0042:0.046;

[0126] The molar ratio of tetrapropylammonium hydroxide, isopropyl alcohol, urea and tetraethoxysilane is 0.3:0.031:0.62:1, and tetraethoxysilane is calculated as SiO2.

[0127] 2) The mixed solution was then placed in a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and the temperature was raised to 180°C at a heating rate of 15°C / h and allowed to stand for crystallization for 2 days. After the crystallization was completed, the reactor was taken out and quickly cooled to room temperature with water, and the crystallized product was centrifuged, washed, and dried. The obtained sample was calcined in a muffle furnace at a temperature of 550°C, a time of 5h, and a heating rate of 100°C / h. Sample C1 was obtained.

[0128] 3) Then weigh NH4Cl and dissolve it in water to prepare a 1 mol / L NH4Cl aqueous solution. Take 1 g of sample C1 and heat it in a water bath at 80°C and a stirring rate of 600 rpm, then add 10 mL of NH4Cl aqueous solution and keep it for 2 hours.

[0129] In the system for ammonium exchange of the ultrathin NaZSM-5 molecular sieve, the mass ratio of sample C1 to 1 mol / L NH4Cl aqueous solution is 1:10.

[0130] 4) After the ammonium exchange is completed, the product is centrifuged and washed, and the ammonium exchange in step 3) is repeated twice. After the product is dried, it is calcined in a muffle furnace at a temperature of 550° C., a time of 5 h, and a heating rate of 100° C. / h to obtain sample C2.

[0131] 5) Then, using tetraammine platinum nitrate as a platinum precursor, platinum was loaded on sample C2 by impregnation method. 1 g of sample C2 was weighed and dispersed in 5 g of H2O and stirred continuously for 2 h, and then 0.004 g of tetraammine platinum nitrate was dissolved in 10 mL of H2O to prepare solution E. Solution E was slowly dripped into the uniformly dispersed ultra-thin HZSM-5 mixed solution under stirring at room temperature.

[0132] In the synthetic platinum metal nanocluster ultra-thin HZSM-5 molecular sieve system:

[0133] The mass ratio of C2 and platinum is 1.0:0.002;

[0134] The mass ratio of sample C2 to the aqueous solution of tetraammineplatinum nitrate is 1:15.

[0135] 6) After continuous stirring at room temperature for 4 h, the product was evaporated and dried, calcined in a tube furnace with flowing air at 350° C. for 2 h at a heating rate of 0.5° C. / min, and then reduced in a hydrogen atmosphere at 300° C. for 2 h at a heating rate of 0.5° C. / min to obtain sample C3.

[0136] The XRD spectrum, SEM and TEM images of sample C3 are similar to those of sample A3 in Example 1, respectively. Figure 1 , Figure 2 and Figure 3 Features in .

[0137] The silicon-aluminum ratio (SiO2:Al2O3) of sample C1 is 1.00:0.0042.

[0138] The mass fraction of platinum in sample C1 is about 0.2%.

[0139] Example 3

[0140] A method for preparing 2-methoxy-4-methylphenol, comprising the following steps:

[0141] Take 0.1 mmol of vanillin, add the molecular sieve sample A3 prepared in Example 1 according to the molar ratio of vanillin to platinum in the catalyst of 500:1, then add 3 mL of H2O, and ultrasonically disperse the system evenly. Place it in an autoclave and replace the air in the autoclave with hydrogen three times. After catalytic reaction at 120°C and 2.0 MPa of H2 for 120 minutes, extract it four times with 1 mL of dichloromethane and detect it using GC.

[0142] The detection results showed that the conversion rate of vanillin was about 100%, and the selectivity of 2-methoxy-4-methylphenol was about 96%.

[0143] Comparative Example 2

[0144] A method for preparing 2-methoxy-4-methylphenol, comprising the following steps:

[0145] Take 0.1 mmol of vanillin, add the molecular sieve sample B3 prepared in Comparative Example 1 according to the molar ratio of vanillin to platinum in the catalyst of 500:1, then add 3 mL of H2O, and disperse the system evenly by ultrasound. Place it in an autoclave and replace the air in the autoclave with hydrogen three times. After the catalytic reaction is carried out at 120°C and 2.0 MPa of H2 conditions for 120 minutes, it is extracted four times with 1 mL of dichloromethane and detected by GC.

[0146] The detection results showed that the conversion rate of vanillin was about 63%, and the selectivity of 2-methoxy-4-methylphenol was about 77%.

[0147] It can be seen that compared with the HZSM-5 molecular sieve with a longer b-axis pore size (sample B3) in Comparative Example 1, the HZSM-5 molecular sieve with a longer b-axis pore size (sample A3) in Example 1 has higher catalytic activity, especially can better catalyze the conversion of vanillin into 2-methoxy-4-methylphenol, with higher conversion rate and selectivity.

[0148] The HZSM-5 molecular sieve provided in the embodiment of the present invention has a good effect in catalyzing the hydrodeoxygenation of vanillin to produce 2-methoxy-4-methylphenol. Specifically, the platinum nanoparticles in the HZSM-5 molecular sieve have good hydrogenation activity, which is beneficial to the conversion of vanillin into vanillyl alcohol, while the flaky HZSM-5 molecular sieve matrix can provide an acidic center to achieve a dehydroxylation process, and the short b-axis of the flaky HZSM-5 molecular sieve matrix can also prevent the intermediate product from reacting with its acidic site, so that the product 2-methoxy-4-methylphenol can be obtained with high selectivity, thereby achieving high activity and high selectivity for preparing 2-methoxy-4-methylphenol by hydrodeoxygenation of vanillin, as well as the stability and sustainability of the catalytic system.

[0149] Furthermore, in the preparation method of the HZSM-5 molecular sieve provided in the embodiment of the present invention, an ultra-thin sheet HZSM-5 molecular sieve matrix is ​​first synthesized, and then platinum is loaded by an impregnation method, so that the required material is obtained in a simple and efficient manner; in addition, mainly by adding urea and regulating the amount of urea, the b-axis pore length of the sheet HZSM-5 molecular sieve matrix can be precisely controlled. The process is simple and easy, and the obtained HZSM-5 molecular sieve has good catalytic activity and selectivity.

[0150] In summary, the flaky HZSM-5 molecular sieve matrix of the present invention can provide acidic centers, and the platinum nanoparticles can provide hydrogenation centers, and the combination of the two can achieve good catalytic activity; and the flaky HZSM-5 molecular sieve matrix has a thinner thickness, that is, a shorter b-axis pore length, which is not only conducive to material diffusion and transmission, but also can greatly reduce the situation where the intermediate product contacts the acidic site and causes side reactions, so it can provide higher product selectivity. The HZSM-5 molecular sieve of the present invention has a particularly good hydrodeoxygenation effect, and in particular, it has a good application prospect in catalyzing the hydrodeoxygenation of bio-oil.

Claims

1. A HZSM-5 molecular sieve, characterized in that: The invention comprises a flaky HZSM-5 molecular sieve matrix and platinum nanoparticles loaded on the flaky HZSM-5 molecular sieve matrix; the average thickness of the flaky HZSM-5 molecular sieve matrix is ​​50-100 nm.

2. The HZSM-5 molecular sieve according to claim 1, characterized in that: The average diameter of the platinum nanoparticles is 8 to 15 nm; And / or, in the HZSM-5 molecular sieve, silicon and aluminum are measured as SiO2 and Al2O3, respectively, and the molar ratio of silicon to aluminum is 1:(0.001-0.02); And / or, in the HZSM-5 molecular sieve, the mass percentage of platinum nanoparticles is 0.1-1%.

3. A method for preparing HZSM-5 molecular sieve, characterized in that: The following steps are involved: A silicon source, an aluminum source, sodium hydroxide, a template, urea, isopropanol and water are mixed, and a crystallization reaction, a first calcination, an ammonium exchange reaction and a second calcination are carried out in sequence to obtain a flaky HZSM-5 molecular sieve matrix; the flaky HZSM-5 molecular sieve matrix is ​​mixed with a platinum source, and a third calcination is carried out to obtain the HZSM-5 molecular sieve as claimed in claim 1 or 2.

4. The preparation method according to claim 3, characterized in that: The silicon source is selected from tetraethoxysilane; and / or, the aluminum source is selected from aluminum nitrate nonahydrate; And / or, the template agent is selected from tetrapropylammonium hydroxide; And / or, the ammonium source used in the ammonium exchange reaction includes ammonium chloride, ammonium nitrate or a combination thereof; And / or, the platinum source includes at least one of tetraammine platinum nitrate, chloroplatinic acid, platinum tetrachloride or dichloroplatinous acid.

5. The preparation method according to claim 3, characterized in that: The silicon source and the aluminum source are measured as SiO2 and Al2O3, respectively, and the molar ratio of the silicon source to the aluminum source is 1:(0.001-0.02); And / or, the silicon source is measured as SiO2, and the molar ratio of the silicon source to the sodium hydroxide is 1:(0.01-0.2); And / or, the silicon source is measured as SiO2, and the molar ratio of the silicon source to the template is 1:(0.1-2); And / or, the silicon source is measured as SiO2, and the molar ratio of the silicon source to the urea is 1:(0.3-2); And / or, the silicon source is measured as SiO2, and the molar ratio of the silicon source to the isopropanol is 1:(0.01-0.2); And / or, the ammonium source used in the ammonium exchange reaction is measured in ammonium, and the usage ratio of the ammonium source to the product of the first calcination is (0.001-0.02) mol: 1 g; And / or, the platinum source is measured as Pt, and the mass ratio of the platinum source to the flaky HZSM-5 molecular sieve matrix is ​​(0.0005-0.01):

1.

6. The preparation method according to claim 3, characterized in that: The temperature of the crystallization reaction is 160-200°C; And / or, the crystallization reaction time is 24 to 72 hours; And / or, the heating rate of the crystallization reaction is 10-20°C / h; And / or, the calcination temperature of the first calcination and the calcination temperature of the second calcination are each independently 500-600° C.; And / or, the holding time of the first calcination and the holding time of the second calcination are each independently 2 to 8 hours; And / or, the heating rate of the first calcination and the heating rate of the second calcination are each independently 80 to 120° C. / h; And / or, the reaction temperature of the ammonium exchange reaction is 60 to 100° C.; And / or, the reaction time of the ammonium exchange reaction is 1 to 4 hours; And / or, the calcination temperature of the third calcination is 300-500° C.; And / or, the holding time of the third roasting is 2 to 8 hours; And / or, the heating rate of the third calcination is 0.1-5°C / min.

7. The preparation method according to claim 3, characterized in that: The third calcination includes a first stage calcination and a second stage calcination; the first stage calcination is carried out in an atmosphere of oxygen-containing gas; the second stage calcination is carried out in an atmosphere of reducing gas; and / or, the calcination temperature of the first stage calcination is 30 to 70° C. higher than the calcination temperature of the second stage calcination; And / or, the ratio of the holding time of the first stage calcination to the holding time of the second stage calcination is 1:(0.5-2).

8. Use of the HZSM-5 molecular sieve as claimed in claim 1 or 2 in catalytic hydrodeoxygenation of bio-oil.

9. A method for preparing 2-methoxy-4-methylphenol, characterized in that: The following steps are involved: The HZSM-5 molecular sieve as claimed in claim 1 or 2 is used as a catalyst and vanillin is used as a substrate to carry out a hydrodeoxygenation reaction to obtain 2-methoxy-4-methylphenol.

10. The preparation method according to claim 9, characterized in that: The hydrodeoxygenation reaction is carried out in a hydrogen atmosphere; The partial pressure of the hydrogen is 1 to 3 MPa; And / or, the reaction temperature of the hydrodeoxygenation reaction is 80 to 160°C; And / or, the reaction time of the hydrodeoxygenation reaction is 30 to 300 minutes; And / or, the molar ratio of the vanillin to the platinum nanoparticles in the HZSM-5 molecular sieve is (400-1000):1; and / or, the hydrodeoxygenation reaction is carried out in water; the mass ratio of the vanillin to the water is 1:(100-400).

Citation Information

Patent Citations

  • Method for preparing 2-methoxy-4-methylphenol from biomass-based vanillin

    CN114656337A

  • ZSM-5 type molecular sieve with nanosheet layer structure as well as preparation and application of ZSM-5 type molecular sieve

    CN117819565A

  • Preparation method of nanosheet-shaped MFI type molecular sieve

    CN118684239A

  • Flat-plate-shaped ZSM-5 supported metal palladium catalyst as well as preparation method and application thereof

    CN118976533A

  • Synergistic co-pyrolysis of biomass and methane for hydrocarbon fuels and chemicals production

    US20180142159A1